Elizabethkingia anophelis Isolated from Patients with Multiple Organ Dysfunction Syndrome and Lower Respiratory Tract Infection: Report of Two Cases and Literature Review - Hu, Shaohua; Jiang, Tao; Zhang, Xia; Zhou, Yajun; Yi, Zhengjun; Wang, Youxi; Zhao, Sishou; Wang, Mingxi; Ming, Desong; Chen, Shicheng (Frontiers in Microbiology, 2017)
Elizabethkingia anophelis, originally discovered from Anopheles mosquito gut, is an emerging pathogen, especially in immunocompromised patients. We isolated two strains of E. anophelis from two separate patients with multiple organ dysfunction syndrome and lower respiratory tract infection. In this paper, we reviewed the status of E. anophelis infection and its antibiotics resistance from reported cases.